European Consensus between Strategy and Principle The Uses of Vertically Comparative Legal Reasoning in Regional Human Rights Adjudication - Theilen, Jens T. (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht,, 2021)
This study offers a critical account of the reasoning employed by the European Court of Human Rights, particularly its references to European consensus. Based on an in-depth analysis of the Court's case-law against the backdrop of human rights theory, it will be of interest to both practitioners and theorists. While European consensus is often understood as providing an objective benchmark within the Court's reasoning, this study argues to the contrary that it forms part of the very structures of argument that render human rights law indeterminate. It suggests that foregrounding consensus and the Court's legitimacy serves to entrench the status quo and puts forward novel ways of approaching human rights to enable social transformation.